SPECTRUM OF ACUTE LEUKEMIAS AND ABERRANT MARKERS EXPRESSION BASED ON FLOWCYTOMETRY IN A TERTIARY CARE CENTRE: Acute Leukemias And Aberrant Markers Expression - Tipu, Hamid Nawaz; Bashir, Muhammad , Mukarram; Altaf, Chaudhry; Noman, Muhammad; Malik, Hamid Saeed (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine frequency of different types of leukemias and aberrant CD markers expression on these types.Study Design: Descriptive study.Place and Duration of Study: Department of Immunology, Armed Forces Institute of Pathology, Rawalpindi from Jul 2015 to Dec 2015.Material and Methods: All peripheral blood and bone marrow samples to confirm the suspicion of acute leukemia with flow cytometric immunephenoltyping were included in the study. Cells were stained with lineage specific monoclonal antibodies against cell specific CD markers through lyse wash procedure. Cell acquisition and analysis was done on Cell Quest software in multi parameter flow cytometer. Data was entered in SPSS v 20.0 to determine the frequencies of different types of leukemias and aberrant CD markers expression.Results: Over 6 months,102 males and 49 females were tested with mean age 26 ± 21 years. Commonest leukemia was AML M2. Among 69 pediatric cases with mean age 7.4 ± 5.8 years, precursor B ALL was commonest. Among 82 adults with mean age 41.5 ± 15.7 years, AML M2 was commonest leukemia. Total 32 cases (18 children and 12 adults) expressed cross lineage aberrant markers, CD13, CD33 and CD7.Conclusion: Aberrant CD markers expression must be kept in mind during lineage assignment of acute leukemias while performing flow cytometric immunophenotyping.